Identification of isoflavonoids in antioxidant effective fraction of Arum rupicola Boiss. leaves - Z Tofighi; Y Shahpar; AR Taheri; S Tavakoli; R Asatouri; M Eftekhari; M Vazirian; MR Shams Ardekani; SN Sadati Lamardi (Institue of Medicinal Plants, ACECR, 2021)
Background: Arum rupicola Boiss. (Araceae Family) is used by the native people of southern areas of Iran as a soup called "kardeh soup". Several flavonoids and phenol compounds have been identified from Arum species. Objective: The aim of this study was to evaluate antioxidant effect and total phenol contents as well as cytotoxic activity of the leaves of A. rupicola. Methods: Antioxidant activity of total methanol extract and fractions including n-hexane, chloroform, ethyl acetate and water residue were evaluated using FRAP and DPPH methods. Total phenol content was measured using Folin-Ciocalteu method. Cytotoxic activity of the extract and fractions were investigated against human breast cancer MCF-7, MDA-MB-231, and T47D cell lines by MTT assay. Further phytochemical isolation was done on the water residue using column chromatography. Results: According to the results, water residue showed the lowest IC50 value (186.7 µg/ml) and the total methanol extract showed the most antioxidant power (163.62 mmol FeSO4/100 g extract) and phenol content (135 µmol Gallic acid/g extract). The hexane fraction also showed the highest cytotoxic effect against MCF-7 breast cancer cell line with IC50 equal to 118.9 μg/ml. Phytochemical analysis of the water residue resulted in isolation and identification of three isoflavonoids named orobol, genistein and genistein 8-c-glucoside. Conclusion: Based on the identification of isoflavonoid compounds in this plant, its ability to be used as a phytoestrogenic supplement can be considered in future studies.